2008
DOI: 10.1002/jmv.21296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype identification of human JC virus in colon cancer in Taiwan

Abstract: Although JC virus (JCV), a human polyomavirus, has been detected in colon cancers, the association between JCV and colon cancer remains controversial. In Taiwan, the prevalence of JCV infection in colon cancer patients has not been reported. Thus, the purpose of this study was to investigate JCV infection in colon cancers in Taiwan. Formalin-fixed, paraffin-embedded tissues from 22 colon cancer patients were examined in this study. Nested PCR was performed to detect viral genomic DNA. The product of the nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 31 publications
0
69
0
Order By: Relevance
“…Human colon cells are susceptible to JCV infection. 5,8 The JCV VLP was able to deliver a suicide gene into human colon cancer cells for expression and subsequently this was able to cause cell death in the presence of GCV as shown in this study. Up to the presence, no effective drug that is able to inhibit JCV replication has been developed.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Human colon cells are susceptible to JCV infection. 5,8 The JCV VLP was able to deliver a suicide gene into human colon cancer cells for expression and subsequently this was able to cause cell death in the presence of GCV as shown in this study. Up to the presence, no effective drug that is able to inhibit JCV replication has been developed.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the JCV DNA has been found in many human tissues including the gastrointestinal track, 10 lung, 11 colon, [5][6][7][8] and esophagus. 9 This indicates that many human tissues maybe susceptible to JCV VLP infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of infection that have been suggested include virus-bearing fluids, contaminated food and water (56,57). The association of JCV with human malignancies is controversial; however, several studies have shown JCV to be associated with human cancers as colorectal-, gastric-, lung-and brain cancers (58)(59)(60)(61)(62). In a study by Flaegstad et al (63), BKV was reported to be expressed in the tissue samples of neuroblastomas, but not found in control tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies, with sample sizes ranging from 18 to 186, detected JCV genomic sequences in 9-89% of colorectal carcinomas and 5-82% of adenomatous tissue (Laghi et al, 1999;Theodoropoulos et al, 2005; R. Hori et al, 2005;Casini et al, 2005;Enam et al, 2002;Goel et al, 2006;P. Y. Lin et al, 2008, Niv et al, 2010aKarpinski et al, 2011;Jung et al, 2008).…”
Section: Cancer In Humanmentioning
confidence: 99%